Marketing Strategies in the Indian Soft Drinks Industry - A Case Study of Pepsico and Coca-Cola Limited - Gupta, M. K.; Neelesh, Sreelata (Indian Journal of Marketing, 2010)
The Indian soft drinks industry has witnessed a radical change in the last few years. In India, after the exit of Coke in 1977, Parle and Pure drinks controlled the soft drinks market. By the end of 1970s, Campa Cola was practically alone in the cola market. Parle introduced Thums Up in the beginning of 1980s. Until 1991, the domestic market was ruled by Parle, with a 60% market share. Its 3 brands - namely Thumps Up, Gold Spot and Limca were the undisputed leaders. The regional brands took up the remaining market. But the market scenario changed drastically when in 1991, Pepsi Foods Limited (PFL) made an entry in India. Since then, the face of Indian soft drinks industry has changed completely. Today, the soft drinks industry in India is dominated by two major players - Pepsi and Coca Cola Limited. Like each industry, this industry too has its own contours of strategies. In the current research paper, effort has been made to identify and elaborate upon the strategies used by these two major players in the Indian market.